Busy tone‐based channel access control for cooperative communication. Issue 10 (11th August 2014) - Xie, Kun; Xie, Kexin; He, Shiming; Zhang, Daqiang; Wen, Jigang; Lloret, Jaime
Abstract Cooperative communication has attracted many research interests in recent years because it can take advantage of the broadcast nature of wireless communications and spatial diversity to improve the network performance. Although relay nodes in cooperative communications can help improve the performance, relay nodes may cause the serious competition on wireless channel accessing, which makes the channel access problem in cooperative communications challenging. To solve this problem, based on cooperative triple busy tone multiple access, this paper proposes a media access control scheme that concurrently combines the request to send/clear to send and busy tone with a proper tone duration timer. In the scheme, three busy tones are proposed to coordinate the nodes in the network to transmit packets, which is further utilised to solve the hidden terminal and exposed terminal problems in cooperative communications. Among the three busy tones, the cooperative busy tone is set according to the relay's signal‐to‐noise ratio. Based on the busy tone, this paper also proposes a bandwidth efficient relay selection algorithm, in which the source node can select the best relay in a distributed way by monitoring the busy tone. The simulation results demonstrate that the proposed scheme can largely reduce the blocking time and improve the channel utilisation in wireless cooperative networks. Copyright © 2014 John Wiley & Sons, Ltd.